SOSIALISASI TENTANG PENTINGNYA MEDIA SOSIAL TERHADAP PERKEMBANGAN SOSIAL DAN PRESTASI SISWA - Nisa, Hannatun; Putri, Hani Amelia; Hasanah, Harkatun; Rahmaniah, Hera Sukma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this day and age, many technologies are developing very rapidly. This can have positive and negative impacts, especially among students. One technology that is often used by students is social media. Social media is a means of information and communication that can make it easier to find out something. information and communication facilities We carry out this service with the aim of understanding and finding out how students at SMAN 1 Praya are utilizing social media, the role of social media and the impact of social media on social development and student achievement. The method used is direct socialization at SMAN 1 Praya Tengah Results from this service is that social media plays an important role in social development and student achievement.